USE OF BANANA PEEL IN FOOD PROCESSING: PROBLEMS OF INEDIBLE COMPONENTS EXTRACTION (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The global production of bananas exceeds 150 million tons annually, generating substantial waste in the form of banana peels, which constitute 35–40% of the fruit’s mass. These peels, rich in dietary fiber (up to 50%), polyphenols, pectin, and minerals, represent a valuable resource for food technologies. However, their utilization is hindered by the presence of antinutritional compounds, such as oxalates (0.1-0.5% dry weight) and cyanides (
Keywords: banana peel; food technology; oxalates; cyanides; extraction methods; functional foods; sustainable production